Phonological working memory and reading in students with dyslexia - de Carvalho, Carolina A. F.; Kida, Adriana de S. B.; Capellini, Simone A.; de Avila, Clara R. B. (Frontiers in Psychology, 2014)
Purpose: To investigate parameters related to fluency, reading comprehension and phonological processing (operational and short-term memory) and identify potential correlation between the variables in Dyslexia and in the absence of reading difficulties. Method: One hundred and fifteen students from the third to eighth grade of elementary school were grouped into a Control Group (CG) and Group with Dyslexia (GDys). Reading of words, pseudowords and text (decoding); listening and reading comprehension; phonological short-term and working memory (repetition of pseudowords and Digit Span) were evaluated. Results: The comparison of the groups showed significant differences in decoding, phonological short-term memory (repetition of pseudowords) and answers to text-connecting questions (TC) on reading comprehension, with the worst performances identified for GDys. In this group there were negative correlations between pseudowords repetition and TC answers and total score, both on listening comprehension. No correlations were found between operational and short-term memory (Digit Span) and parameters of fluency and reading comprehension in dyslexia. For the sample without complaint, there were positive correlations between some parameters of reading fluency and repetition of pseudowords and also between answering literal questions in listening comprehension and repetition of digits on the direct and reverse order. There was no correlation with the parameters of reading comprehension. Conclusion: GDys and CG showed similar performance in listening comprehension and in understanding of explicit information and gap-filling inference on reading comprehension. Students of GDys showed worst performance in reading decoding, phonological short-term memory (pseudowords) and on inferences that depends on textual cohesion understanding in reading. There were negative correlations between pseudowords repetition and TC answers and total score, both in listening comprehension.